Systematic correlation between ligand length, bandgap energy and Seebeck voltage of Fe-based spincrossover (SCO) metal complexes through optical characterization - Hassan, H. C.; Said, S. M.; Noor, I. M.; Megat Hasnan, M. M. I.; Zakaria, R.; Nik Ibrahim, N. M. J.; Salleh, F.; Fadzallah, I. A.; Md. Noor, N. L.; Abdullah, N. (Taylor and Francis, 2023)
Fe-based spincrossover (SCO) molecular complexes have shown to exhibit spincrossover behavior when subjected to stimuli such as heat, light and pressure. In a previous work, solutions of Fe-based spincrossover (SCO) molecular complexes with increasing ligand length, CnH2n+1NH2 (n = 12, 14, 16) of Fe(L12)2](BF4)2, Fe(L14)2(BF4)2, and Fe(L16)2(BF4)2, have shown to produce ultrahigh Seebeck coefficients when subjected to a temperature gradient. In this work, these three compounds are dissolved in dimethyl sulfoxide (DMSO) and subjected to temperature dependent Ultraviolet-visible (UV-vis) spectrometry. This optical characterization method was used to provide a correlation between the ligand length of the SCO complex and the bandgap energy measured. Subsequently, these findings were also triangulated with the effect of the ligand length on ionic conductivity and the Seebeck voltage. This work thus provides a systematic molecular understanding of the optical and electronic characteristics of SCO complexes, which paves the way for molecular design strategies in utilization of SCO for applications such as energy conversion and sensors.